Atherosclerotic plaque injury-mediated murine thrombosis models: advantages and limitations. (18th May 2020) - Karel, MFA; Hechler, B.; Kuijpers, MJE; Cosemans, JMEM
Abstract: In spite of current treatment strategies, myocardial infarction and stroke are still major causes of death worldwide. These events are triggered by damage of an atherosclerotic plaque, resulting in occlusive thrombus formation. Mouse studies have significantly contributed to our understanding of the mechanisms of atherogenesis and of thrombosis following plaque injury, but the extent to which the mouse serves as an accurate model of human disease is open to discussion. In this review, we provide a detailed overview and comparison of the described mouse models for atherothrombosis including their (dis)advantages. Herein guidance is provided on how to select a suitable atherothrombosis model for research questions primarily relevant to the field of thrombosis.